The role of circular economy in supporting sustainable development goals (SDGs) in Indonesia from an Islamic economic perspective - Ni’mah, Iffatun; Rokhim, Abdul; Musari, Khairunnisa (Journal of Islamic Economics Lariba, 2024)
IntroductionHuman life is currently in a critical situation regarding environmental awareness. Discussions on sustainable development have become a key topic in building sustainable SDGs to achieve environmental preservation. Sustainable development is a crucial benchmark of environmental conservation.ObjectivesThis study aims to explain how the use of circular economy strategies can achieve sustainable development goals in line with the SDGs from an Islamic economic perspective.MethodThis study employed a qualitative literature review method. Secondary data sources, such as books, scientific journals, and previous articles, form the basis for analyzing various issues related to circular economy strategies and sustainable development.ResultsThe findings indicate that the circular economy plays an important role in supporting sustainable development goals in Indonesia, particularly in achieving SDG goal number 8, which aims for sustainable, inclusive economic growth and the creation of decent work for all. Additionally, the circular economy is closely related to achieving SDG goal number 12, which ensures sustainable consumption and production patterns. Islamic economics plays a crucial role in supporting the implementation of SDGs in Indonesia by involving various products and ecosystems, including Sharia-compliant financial products, halal food and beverages, Islamic entrepreneurs, and the circular economy related to resource utilization.ImplicationsThe results highlight the importance of the circular economy as a strategic approach for addressing environmental challenges and achieving long-term sustainability. The integration of Islamic economic principles offers a robust framework to promote ethical and responsible resource management.Originality/NoveltyThis study provides a unique perspective by combining the concepts of circular economy and Islamic economics to explore their combined impact on achieving sustainable development goals. This contributes to a broader understanding of how cultural and religious principles can enhance sustainability.